Collaborating to offer HPV vaccinations in jails: results from a pre-implementation study in four states - Amanda Emerson; Molly Allison; Lisa Saldana; Patricia J. Kelly; Megha Ramaswamy (BMC, 2021)
Abstract Background Correctional facilities are an underutilized venue for reaching young adults who have not vaccinated for human papillomavirus (HPV). The objective of this study was to identify factors that are associated with jail and local health department (LHD) interest in partnering to offer HPV vaccinations to young adults in jail. Methods Consolidated framework for implementation research (CFIR)-guided surveys were conducted with jail administrators in Iowa, Kansas, Missouri, and Nebraska, September 2017-October 2018. Jail survey data were analyzed using chi square distribution and relative risk regression. Using data from sister surveys conducted with LHD administrators in the same counties (results previously reported), we identified characteristics of counties in which both the jail and LHD indicated interest in collaborating to offer HPV vaccinations in the jail. Results Jail survey response was 192/347 (55.3%). Surveys with LHDs yielded 237/344 (68.9%) responses. Eleven communities were identified where both the jail and LHD expressed interest. Only "any vaccines provided in jail" predicted shared interest (RR: 5.36; CI: 2.52-11.40; p < .01). For jail administrators, offering other vaccines was 3 times (CI:1.49-6.01; p < .01) and employing a nurse 1.65 times more likely (CI: 1.20-2.28; p < .01) to predict interest in collaborating to offer HPV vaccination. Open-ended responses indicated that managing linkages and stakeholder investment were areas of emphasis where collaborations to provide vaccinations in the jails had been previously implemented. Conclusions Interest in jail-LHD partnerships to provide HPV vaccinations in jails exists in the Midwest but will require building-out existing programs and linkages and identifying and strengthening shared values, goals, and benefits at all levels.